Current Topics (The Muslim world, 1933)
Iraq now a Nation The Bible in Hausa Stop Polygamy by Legislation Opposition on Arabia's Frontiers Political Meetings in Mosques The Turkish Press in Bulgaria Koran Ritual halts Trial in New York The Radio in Egypt Wireless Stations for Iraq Pipelines Prayer should be in Arabic “After the first verse” in St. Mark Reply to Professor Margoliouth's Article, Jan., 1933